2010
DOI: 10.1371/journal.pntd.0000860
|View full text |Cite
|
Sign up to set email alerts
|

Annual Incidence of Snake Bite in Rural Bangladesh

Abstract: BackgroundSnake bite is a neglected public health problem in the world and one of the major causes of mortality and morbidity in many areas, particularly in the rural tropics. It also poses substantial economic burdens on the snake bite victims due to treatment related expenditure and loss of productivity. An accurate estimate of the risk of snake bite is largely unknown for most countries in the developing world, especially South-East Asia.Methodology/Principal FindingsWe undertook a national epidemiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
142
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(164 citation statements)
references
References 10 publications
19
142
3
Order By: Relevance
“…5 As evident in our study 189 patients (50.26%, n=376) were administered anti snake venom but later found that there was no envenoming. This is due to the fact that snake bite being a life threatening event the treating physician would prefer to err on the safer side rather than not taking the chance at all.…”
Section: Discussionsupporting
confidence: 48%
“…5 As evident in our study 189 patients (50.26%, n=376) were administered anti snake venom but later found that there was no envenoming. This is due to the fact that snake bite being a life threatening event the treating physician would prefer to err on the safer side rather than not taking the chance at all.…”
Section: Discussionsupporting
confidence: 48%
“…16,19 It was encouraging to know that in the present study 364 (91%) of the participants did not consider going to a faith healer or quack as a treatment option after snake bite, this finding was similar to the study done by Pandey et al 4 While in other similar studies 86% of snakebite victims in Bangladesh, 75% in Pakistan, and 61% in Maharashtra, India still visit traditional healers. [20][21][22] In the present study it was found that 305 (76.25%) of the total participants offer milk to snakes brought by local Snake charmers on Nag Panchami festival which proves detrimental to the snake's health. Therefore awareness camps in laying emphasis on imparting basic knowledge about snake identification, snakebite prevention and clearing misconceptions should be held in schools, proper first aid methods for snakebites should be demonstrated through various outreach activities and increased awareness about snake and snakebite identification among heath care workers and general population should also be done.…”
Section: Discussionmentioning
confidence: 89%
“…Community-based surveys are especially valuable in that they lack the statistical biases inherent in hospital-based surveys. 8,9 ii) increasing access to antivenoms, particularly in rural areas, through mechanisms geared towards facilitating antivenom deployment, such as maintaining the cold chain (in the case of liquid antivenoms), sharing it with vaccination programmes, or improving coordination between rural health posts and central governmental offices. The clinical management of envenomings in primary-health-care facilities should be promoted.…”
Section: Other Mitigating Measuresmentioning
confidence: 99%
“…Of those who are bitten, approximately 125 000 die and around 400 000 are left with permanent sequelae. 2,3,6,7 However, more recent nationwide community-based surveys in Bangladesh and India have shown that the scale of this problem is far greater than suggested by hospital-based statistics 8,9 and that these global figures greatly underestimate the actual incidence of snakebite envenoming and the resulting mortality and disability.…”
Section: Introductionmentioning
confidence: 99%